Irradiation Time Optimization on Photocatalytic Activity of Nanoparticles MgO from Dolomite Bangkalan - Rohmawati, Lydia; Fathoni, Silviana Nurul; Setyarsih, Woro; Putri, Nugrahani Primary; Darminto, Darminto (Trends in Sciences, 2024)
Dolomite is a type of sedimentary rock material that is often found in the Bangkalan Madura area. This dolomite has a higher MgO compound content than in the other areas, namely 40 %, but its utilization has only been as fertilizer and building materials. For this reason, this research aims to determine the characteristics of MgO nanoparticles and their application in photocatalytic with visible light irradiation. The synthesis of MgO nanoparticles used the hydrochloric acid leaching method, and the results were characterized by X-ray diffraction, Fourier transform infrared, Scanning electron microscopy, Transmission electron microscopy, Raman spectroscopy, Photoluminescence, and Ultraviolet-visible spectroscopy. The results showed that the synthesized MgO nanoparticles had a periclase phase and were shaped like a spherical cube with an average nanoparticle size of 27 nm and an energy gap of 3.9 eV. The optical properties of the MgO nanoparticles showed quite strong luminescence at a Raman shift of 1,087.36 cm−1, which was associated with the type of vibrational waves in the atomic lattice, and there were surface defects on the surface of the MgO nanoparticles, namely in the emission spectra of 720.06 and 740.39 nm originating from oxygen vacancies (F-center) and Mg vacancies (V-center). The photocatalytic activity of MgO nanoparticles in visible light showed the optimum time to degrade 30 ppm methylene blue dye in 360 min and yielded a degradation percentage of 99 %. Therefore, MgO nanoparticles could be used for processing industrial dye waste using visible light. HIGHLIGHTS The synthesis of MgO Nanoparticles from Bangkalan dolomite used the hydrochloric acid leaching method The presence of nanocrystallite size, crystal defects, and oxygen vacancies in MgO nanoparticles can increase photocatalytic activity MgO nanoparticles can degrade methylene blue dye with an optimum time of 360 minutes under visible light irradiation GRAPHICAL ABSTRACT